2010
DOI: 10.1136/jech.2010.122333
|View full text |Cite
|
Sign up to set email alerts
|

Are socio-economic disparities in diet quality explained by diet cost?

Abstract: Background Socioeconomic disparities in nutrition are well documented. This study tested the hypothesis that socioeconomic differences in nutrient intakes can be accounted for, in part, by diet cost. Methods A representative sample of 1,295 adults in King County (WA) was surveyed in 2008–2009 and usual dietary intakes were assessed based on a food frequency questionnaire (FFQ). Monetary value of individual diets was estimated using local retail supermarket prices for 384 foods. Nutrients of concern as identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 48 publications
4
97
2
2
Order By: Relevance
“…Browning and Crossley (2009) demonstrated that this distribution did, in fact, change and Griffith et al (2013) confirmed this change for UK households during the recent economic recession; more specifically, households bought fewer and cheaper calories and thus reduced the nutritional quality of the foods they purchased. Other researchers have corroborated this finding of obesogenic and poorer quality diets in response to unemployment (Drewnowski, 2010;Monsivais et al, 2011Monsivais et al, , 2012Liu et al, 2013). Finally, health researchers have also addressed the implications of unemployment for human health by assessing risk factors such as obesity (Darmon and Drewnowski, 2008), excessive alcohol consumption (Dee, 2001;Mossakowski, 2008), smoking habits (Fagan et al, 2007), medical care (World Bank, 2009), reduced physical activity in leisure time (Grayson, 1993) and mental health (Urbanos-Garrido and López-Valcárcel, 2015).…”
Section: Introductionmentioning
confidence: 67%
“…Browning and Crossley (2009) demonstrated that this distribution did, in fact, change and Griffith et al (2013) confirmed this change for UK households during the recent economic recession; more specifically, households bought fewer and cheaper calories and thus reduced the nutritional quality of the foods they purchased. Other researchers have corroborated this finding of obesogenic and poorer quality diets in response to unemployment (Drewnowski, 2010;Monsivais et al, 2011Monsivais et al, , 2012Liu et al, 2013). Finally, health researchers have also addressed the implications of unemployment for human health by assessing risk factors such as obesity (Darmon and Drewnowski, 2008), excessive alcohol consumption (Dee, 2001;Mossakowski, 2008), smoking habits (Fagan et al, 2007), medical care (World Bank, 2009), reduced physical activity in leisure time (Grayson, 1993) and mental health (Urbanos-Garrido and López-Valcárcel, 2015).…”
Section: Introductionmentioning
confidence: 67%
“…Nesses estudos, todos realizados em mercados com economias desenvolvidas e com cenários de consumo alimentar e preços muito diferentes do brasileiro, a imposição de uma redução ao valor médio da dieta acarretou em elevação de sua densidade energética. Desse modo, famílias de baixa renda ou com orçamento restrito, buscando minimizar seu gasto com alimentos, seriam direcionadas a fazer escolhas alimentares menos saudáveis, de maior densidade energética, no intuito de atingir a necessidade energética mínima dentro das restrições estabelecidas por seu orçamento 14,15 . A verificação dessa relação na população brasileira é particularmente importante, uma vez que grande contingente da população ainda possui rendimentos abaixo dos patamares ideais.…”
Section: Introductionunclassified
“…Individual food-related practices (e.g. shopping and food preparation) may be strongly shaped by external influences such as socioeconomic status, and new approaches such as mapping area distribution of house prices, may help to understand in a better manner the intersection between individuals and environments (34) . Approaches such as this are starting to illustrate that previously underexplored factors (e.g.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%